Acid buffering capacity of four contrasting metal-contaminated calcareous soil types: Changes in soil metals and relevance to phytoextraction. (October 2020) - Wang, Zinan; Jia, Mingyun; Li, Zhu; Liu, Hongyan; Christie, Peter; Wu, Longhua
Abstract: Four different metal-contaminated calcareous soil types, Carbonati-Perudic Cambosols (CPC), Fe-accumuli-Stagnic Anthrosols (FSA), Ochri-Aquic Cambosols (OAC) and Calci-Orthic Aridosols (COA), were investigated. The acid buffering capacity and metal-releasing behaviors of the soils were explored using an acid extraction method. Soil incubation and pot experiments were conducted to investigate changes in soil metal speciation and the enhancement of phytoextraction by soil acidification. There were several to tens of times differences in acid buffering capacities between soils. Soil calcium content may represent the major buffering system as indicated by significant linear correlations between the amount of Ca 2+ released and H + addition, and metal release into solution with H + addition showed three stages, i.e. little release, slow release and rapid release stages. Soil carbonate-bound and Fe/Mn oxide-bound Cd and Zn decreased with the addition of H + to all four soils, but organic matter-bound and residual metals remained unchanged. Based on the intensity of acidification, the efficiency Cd and Zn phytoextraction increased substantially with the addition of H + in the case of the CPC but not the FSA which had a higher acid buffering capacity than the CPC. Hence, it may be concluded that the acid buffering capacity and changes in soil metal fractions with acidification of contaminated calcareous soil types should be determined before phytoextraction of these soils is attempted. Graphical abstract: Image 1 Highlights: The acid buffering capacity of a calcareous soil is mainly indicated by the Ca content. Metal release induced by soil acidification followed the pattern: little-slow-fast stages. Acidification can enhance plant uptake of carbonate- and Fe/Mn oxide-bound Cd. Abstract : Soil metal availability is correlated with soil acid buffering capacity: soil acidification and relevance to phytoextraction.